IDENTIFICATION OF VEHICLE AND ROAD PARAMETERS TOWARDS TRAFFIC MODELLING IN NETWORK ENVIRONMENT - Vase Jordanoska; Darko Danev; Aleksandar Kostikj (Proceedings of 26th JUMV International Automotive Conference Science & Motor Vehicles, 2017)
Traffic congestion is one of the biggest issuethatpeople are facing with. Increased traffic flow implies to increased pollution, which affects people’s health and the environment. In such conditions arises theneedfor planning and improving of traffic flows in urban areas, but also at motorways. Traffic modeling and simulation tools have significant role in achieving these goals. The inclusion of vehicle dynamics aspects in these tools is analyzed, because this research field is multidisciplinaryand includes aspects from different scientific areas. The findings show that there is a space for improving of traffic models by adding vehicle / road parameters which will result in more realistic presentation of vehicle behavior.
Keywords: Traffic Flow, Vehicle Dynamics, Vehicle and Road Parameters, Model, Simulation